G6PD testing in support of treatment and elimination of malaria: recommendations for evaluation of G6PD tests. - Domingo, G; Satyagraha, A; Anvikar, A; Baird, K; Bancone, G; Bansil, P; Carter, N; Cheng, Q; Culpepper, J; Eziefula, C; Fukuda, M; Green, J; et al. (2013)
Malaria elimination will be possible only with serious attempts to address asymptomatic infection and chronic infection by both Plasmodium falciparum and Plasmodium vivax. Currently available drugs that can completely clear a human of P. vivax (known as "radical cure"), and that can reduce transmission of malaria parasites, are those in the 8-aminoquinoline drug family, such as primaquine. Unfortunately, people with glucose-6-phosphate dehydrogenase (G6PD) deficiency risk having severe adverse reactions if exposed to these drugs at certain doses. G6PD deficiency is the most common human enzyme defect, affecting approximately 400 million people worldwide.Scaling up radical cure regimens will require testing for G6PD deficiency, at two levels: 1) the individual level to ensure safe case management, and 2) the population level to understand the risk in the local population to guide Plasmodium vivax treatment policy. Several technical and operational knowledge gaps must be addressed to expand access to G6PD deficiency testing and to ensure that a patient's G6PD status is known before deciding to administer an 8-aminoquinoline-based drug.In this report from a stakeholder meeting held in Thailand on October 4 and 5, 2012, G6PD testing in support of radical cure is discussed in detail. The focus is on challenges to the development and evaluation of G6PD diagnostic tests, and on challenges related to the operational aspects of implementing G6PD testing in support of radical cure. The report also describes recommendations for evaluation of diagnostic tests for G6PD deficiency in support of radical cure.